Art Music by Caribbean Composers: Bahamas - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2011)
The cultural identity of the Bahamas owes much to its West African and British colonial heritages and to its physical proximity to the United States. A combination of African and European elements - rhyming spirituals, anthems, rushin' music at watch-night services, wake and setting-up songs; ringplays, fire dance, jump-in-dance, quadrille music (rake-‘n’-scrape music), goombay, and junkanoo - can be seen in musical traditions throughout the Caribbean, including art music.